A Crusade Gone Wrong: George W. Bush and the War on Terror in Asia. (January 2015) - Ray, Saumyajit
President George W. Bush regarded the war on terror he unleashed in Afghanistan and Iraq as a war of ideas just as it was a war of arms. With evangelical zeal and through his policy of regime change, he wanted to introduce Western-type liberal democracy in both countries but failed in the attempt. Though "democratically"-elected governments took office in Kabul and Baghdad, the American occupation was strongly resisted in both places, leading to the emergence of new insurgencies (Iraq) and the gradual regrouping of militants dislodged from power (Afghanistan). Not only did the United States under Bush fail to prevent Pakistan from aiding Afghan militants, it helped Shi'ite Iran in gaining an unprecedented foothold in the affairs of the new Shia-led dispensation in Iraq. George W. Bush's surge for democracy through military intervention in Afghanistan and Iraq resulted in a new wave of anti-Americanism in those regions and provided a fresh lease of life to Islamic fundamentalism. His crusade had indeed gone wrong.